TRAINING ON MENU PREPARATION FOR BREAST MILK VOLUME FORMATION IN BREASTFEEDING MOTHERS - Marniati; Enda Silvia Putri; Itza Mulyani; Sufyan Anwar (RADJA PUBLIKA, 2023)
Breast milk is the original fluid secreted from the breast after the mother gives birth, which is a flexible and easily available food without special preparation with a temperature that suits the baby. The problem in this service is the low coverage of exclusive breastfeeding in the working area of the Johan Pahlawah health center based on data from the West Aceh Health Office, namely with an achievement of 65%, to 44% (West Aceh District Health Office, 2020, 2021). The purpose of this service is to increase mothers' knowledge about breastfeeding their babies with the goal of achieving the exclusive breastfeeding coverage target of 80%. The method used in this service is the socialization method (pree-test and post-test) and Intervention (menu preparation training) for the formation of breast milk volume in cadres and breastfeeding mothers. Based on the results of the service with the Pree-test and Post-test methods on Training on Menu Formation of Asi Volume, an increase in the average value of respondents' knowledge before and after socialization was obtained, where the pree test results showed 83% of mothers had good knowledge, while the post test increased the mother's knowledge, namely 91%, meaning that socialization is able to increase the mother's knowledge so that if it continues to be implemented it will be able to change the mother's behavior into behavior that can increase the mother's knowledge to give Asi to her baby. The next method is the Intervention on Training on the Preparation of Volume-Building Menus for Breastfeeding Mothers. The result of the intervention is that the mother enthusiastically participates in the activity from the beginning to the end of the intervention activity and can accept the menu provided. In conclusion, based on the results of the service that it is very important for the gampoeng apparatus to support the activities of cadres to continue this service model in order to reduce the coverage rate of exclusive breastfeeding.